Outcome of Well-Differentiated Thyroid Carcinoma Patients Receiving a Cumulative Doses of ? 600 mCi (22GBq) of I-131 (Bangladesh Journal of Nuclear Medicine, 2016)
Background: There is no maximum limit for cumulative dose of I-131 for persistent disease in well-differentiated thyroid carcinoma (DTC) patients. However, most remissions are obtained with cumulative activity equal to or lower than 600 mCi (22 GBq). On the other hand a significantly increased risk of leukemia and secondary cancers has been reported with high cumulative dose of I-131 (? 600 mCi). Above this cumulative activity further radioiodine therapy should be taken on an individualized basis.Objective: The aim of the study was to see the outcome of patients with well differentiated thyroid carcinoma receiving a cumulative doses (CDs) of ? 600 mCi I-131.Patient and Method: A retrospective study of 72 patients with DTC receiving a CDs of ?600 mCi I-131 in the National Institute of Nuclear Medicine and Allied Sciences (NINMAS), Dhaka during the period of January 1994 up to December 2007 was carried out. Initially all patients were treated by thyroidectomy followed by radioiodine therapy as adjusted by standard protocol. The mean period of follow up was 8.9 ± 6 years.  From the medical files, age, gender, histopathological variant, thyroid remnant and radio ablation doses, follow up data were recorded. Age was further categorized as 5 doses to find its association with status on last follow up. Disease free (DF) was established as: undetectable or suppressed serum Tg levels